Wellness in STEM pathways: Exploring the challenges and supports for historically underserved STEM undergraduates beyond grades - Kumar, Ramya; Nardo, Jocelyn; Ewell, Sharday; Fluker, Jordan; Harvey, Alayna; Rivera, Angelita; Ballen, Margarette; Salehi, Shima (American Journal of STEM Education, 2026)
Historically underserved STEM undergraduates face interconnected barriers that affect academic success and well-being. This exploratory survey study investigates: (1) What challenges compromise historically underserved students’ wellness, and what resources help them cope? (2) How do students perceive institutional practices as supporting or hindering their well-being? Findings show Black, Indigenous, People of Color (BIPOC) students often feel excluded in predominantly white spaces, and gender-marginalized students report similar isolation. Identity-based organizations are key emotional and social supports. First-generation students struggle to meet academic demands but benefit from transition programs and advising, while low-income students face financial barriers to enrichment. Participants report limited confidence in institutions’ commitment to equity, underscoring the need for coordinated, campus-wide, wellness-focused reforms within the United States.